Profil Risiko dan Imbal Hasil pada Perusahaan Pemerintah: Bukti Empiris dari Bursa Efek Indonesia - Ringkot P. Nainggolan; Rexon Nainggolan (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study investigates the effect of government ownership on the risk-return profile of firms listed on the Indonesia Stock Exchange (IDX). Using a comprehensive sample of 600 companies, this research employs the Capital Asset Pricing Model (CAPM) framework to examine financial performance from the perspectives of risk-adjusted return (Alpha), systematic risk (Beta), and total volatility (Standard Deviation). The sample is divided into two parts, namely government-owned companies (n=33) and non-government companies (n=567). Statistical analysis using the T-Test and Welch T-Test reveals three main findings. First, there is no significant difference in Alpha between the two groups, indicating that government ownership does not result in a systematic performance penalty or premium after risk adjustment. Second, government-related companies exhibit much higher Beta coefficients, indicating greater sensitivity to market movements than non-government companies. Third, although they have higher systematic risk, there is no significant difference in total volatility (Standard Deviation) between the two groups. This indicates a risk-sharing phenomenon where the increased market sensitivity of government companies is offset by lower idiosyncratic risk. These results indicate that on the IDX, ownership structure is a determinant of the risk borne by investors but plays a lesser role in determining risk-adjusted returns.